Drug product development for the back of the eye - Kompella, Uday B.; Edelhauser, Henry F. (Springer eBooks., 2011)
This comprehensive volume discusses approaches for a systematic selection of delivery systems for various classes of therapeutic agents including small molecule, protein, and nucleic acid drugs. Specific topics covered in this book include: Solution, suspension, gel, nanoparticle, microparticle, and implant dosage forms Refillable and microneedle devices Intravitreal, suprachoroidal, intrascleral, transscleral, systemic, and topical routes of delivery Physical methods including iontophoresis for drug delivery Rational selection of routes of administration and delivery systems Noninvasive and continuous drug monitoring Clinical endpoints and regulatory path to drug product development Emerging and existing drugs and drug targets   Drug Product Development for the Back of the Eye is authored by renowned ocular drug delivery experts, representing academic, clinical, and industrial organizations and serves as indispensable resource for ophthalmic researchers, drug formulation scientists, drug delivery and drug disposition scientists, as well as clinicians involved in designing and developing novel therapeutics for the back of the eye diseases. This book is also relevant for students in various disciplines including ophthalmology, pharmaceutical sciences, drug delivery, and biomedical engineering.   Uday B. Kompella, Ph.D., Professor of Pharmaceutical Sciences & Ophthalmology, University of Colorado, developed functionalized nanoparticles, nanoporous microparticles, microparticles, injectable implants, dendrimers, liposomes, and in situ forming gels for the eye. He is a Fellow of the American Association of Pharmaceutical Scientists (2005) and the Association for Research in Vision and Ophthalmology (2010). He received Distinguished Scientist (2006) Award from the University of Nebraska.   Henry F. Edelhauser, Ph.D., Professor of Ophthalmology, Emory University, made pioneering contributions towards transcorneal, transscleral, and suprachoroidal drug delivery to the eye. He is a recipient of the Castroviejo Medal and the Alcon Research Award (1999), American Academy of Ophthalmology Senior Achievement Award (2000), and the Procter Medal (2005) for his outstanding ophthalmic translational research. He served as the president of the Association for Research in Vision and Ophthalmology (1990-91).